1971
DOI: 10.1002/anie.197105371
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Carbenes by Photochemical Cycloelimination

Abstract: A wide variety of shelf stable substrates undergo photochemical cycloelimination under relatively mild conditions. Suitable substrates include cyclopropanes, oxiranes, aziridines, and diazirines, as well as 3 H‐pyrazoles and 1,3‐dioxolanes. Carbenes prepared from these substrates as well as certain cyclic carbonates, sulfites, and phosphoranes behave chemically in a manner similar to divalent carbon species produced from conventional diazo precursors, namely, they react with alkenes to give cyclopropanes and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…[3]) may provide an important photochemical decomposition pathway in simple cyclopropenes with high singlet excitation energies (14). Carbene photoextrusions are rather common in cyclopropane photochemistry (23,24) (particularly in alkyl-substituted systems) (24), but have apparently not been observed in cyclopropene systems.…”
Section: + A+a+m+mentioning
confidence: 99%
“…[3]) may provide an important photochemical decomposition pathway in simple cyclopropenes with high singlet excitation energies (14). Carbene photoextrusions are rather common in cyclopropane photochemistry (23,24) (particularly in alkyl-substituted systems) (24), but have apparently not been observed in cyclopropene systems.…”
Section: + A+a+m+mentioning
confidence: 99%
“…In all cases the corresponding ozonides, 70a-c, have been shown to be stable under the reaction conditions, whereas preliminary experiments suggested that small amounts of water in the reaction medium can result in the formation of carbonyl products, possibly through interception of the intermediate radical cations [164]. An alternative explanation, accounting for the formation of carbonyl compounds, might involve cleavage of the intermediate carbonyl ylides, as actually suggested in Griffin's work on the photoelimination of aryloxiranes [165]. HPLC analysis indicated that BP was not appreciably consumed during these photooxygenations, and that the epoxides were not oxidized upon irradiation for long time with a 400-W high-pressure sodium lamp in oxygenated-acetonitrile solutions containing RB as triplet exicited sensitizer.…”
Section: Cosensitized Cyanoaromatic-sensized Photooxygenation Of Orgamentioning
confidence: 91%
“…The light‐induced ring‐opening process of oxirane‐based molecules has been studied for over half a century now, [1,2] yet still, there are many unanswered questions relating to a number of processes involved. This includes which bond in the three‐membered ring is most likely to be broken, what exact mechanism is followed as the molecule opens up and how different substituents affect the process [3–6] . One molecule which exhibits a number of these issues is the diphenyl substituted oxirane‐based trans ‐stilbene oxide ( trans ‐2,3‐diphenyloxirane), which will be the focus of the study presented here.…”
Section: Introductionmentioning
confidence: 99%
“…In cases in which the ring‐opening mechanism of oxiranes proceeds via the C−C bond, Woodward‐Hoffman (WH) rules generally describe the process well [3,4,10,16,18–20] . Interestingly, in their seminal papers describing the conservation of orbital symmetry of concerted reactions, [18,19] Woodward and Hoffman themselves explicitly discuss the thermal‐ and photo‐induced ring‐opening and closing of oxirane via the C−C bond – despite the C−O bond opening mechanism being the more common pathway for the unsubstituted oxirane molecule [2,3,7–10] .…”
Section: Introductionmentioning
confidence: 99%